The paris daughter eaudiobook - Harmel, Kristin (Simon & Schuster Audio, 2023)
Instant New York Times bestseller! "A gorgeous, gut-wrenching" (Kate Quinn, New York Times bestselling author) historical novel about two mothers facing unthinkable choices as the Nazis invade France—from the New York Times bestselling author Kristin Harmel. Paris, 1939: Young mothers Elise and Juliette become fast friends the day they meet in the beautiful Bois de Boulogne. Though there is a shadow of war creeping across Europe, neither woman suspects that their lives are about to irrevocably change. When Elise becomes a target of the German occupation, she entrusts Juliette with the most precious thing in her life—her young daughter, playmate to Juliette's own little girl. But nowhere is safe in war, not even a quiet little bookshop like Juliette's Librairie des Rêves, and, when a bomb falls on their neighborhood, Juliette's world is destroyed along with it. When the war finally ends, Elise returns to reunite with her daughter, only to find her friend's bookstore reduced to rubble—and Juliette nowhere to be found. What happened to her daughter in those last, terrible moments? Juliette has seemingly vanished without a trace, taking all the answers with her. Elise's desperate search leads her to New York—and to Juliette—one final, fateful time. A sweeping celebration of resilience, motherhood, and love, The Paris Daughter is "historical fiction at its best" (Sadeqa Johnson, New York Times bestselling author).